Etiology and Antimicrobial Resistance of Culture-Positive Infections in Ugandan Infants: A Cohort Study of 7000 Neonates and Infants - Davies, Hannah G; Kyohere, Mary; Tusubira, Valerie; Amone, Alexander; Wamawobe, Amusa; Komugisha, Cleophas; Musoke, Philippa; Hookham, Lauren; Ravji, Pooja; Etti, Melanie; Nsimire Sendagala, Juliet; Shelley, Dan R; et al. (Oxford University Press, 2025)
Epidemiological evidence about the etiology and antimicrobial resistance of neonatal infections remains limited in low-resource settings. We aimed to describe the etiology of neonatal infections in a prospective observational cohort study conducted at two hospital sites in Kampala, Uganda.BackgroundEpidemiological evidence about the etiology and antimicrobial resistance of neonatal infections remains limited in low-resource settings. We aimed to describe the etiology of neonatal infections in a prospective observational cohort study conducted at two hospital sites in Kampala, Uganda.Babies admitted to either unit with risk factors or signs of sepsis, pneumonia, or meningitis had a blood culture, nasopharyngeal swab, and lumbar puncture (if indicated) collected. Basic demographics were collected, and babies were followed up until discharge or death to determine admission outcome. Blood cultures were processed using the BACTEC system and identification confirmed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Cerebrospinal fluid was processed using standard microbiological testing and swabs were processed using the multiplex real-time polymerase chain reaction assay. Antimicrobial susceptibilities of bacterial isolates to World Health Organization-recommended first-line antibiotics (ampicillin or benzylpenicillin and gentamicin) were assessed using e-tests.MethodsBabies admitted to either unit with risk factors or signs of sepsis, pneumonia, or meningitis had a blood culture, nasopharyngeal swab, and lumbar puncture (if indicated) collected. Basic demographics were collected, and babies were followed up until discharge or death to determine admission outcome. Blood cultures were processed using the BACTEC system and identification confirmed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Cerebrospinal fluid was processed using standard microbiological testing and swabs were processed using the multiplex real-time polymerase chain reaction assay. Antimicrobial susceptibilities of bacterial isolates to World Health Organization-recommended first-line antibiotics (ampicillin or benzylpenicillin and gentamicin) were assessed using e-tests.A total of 7323 infants with signs or risk factors for sepsis had blood cultures, 2563 had nasopharyngeal swabs, and 23 had lumbar punctures collected. Eleven percent of blood cultures and 8.6% of swabs were positive. Inpatient mortality was 12.1%, with 27.7% case fatality observed among infants with Gram-negative bloodstream infections. Escherichia coli (14.8%), Acinetobacter spp. (10.3%), and Klebsiella spp. (7.6%), were notable contributors to Gram-negative sepsis, whereas Group B Streptococcus was the predominant Gram-positive pathogen identified (13.5%). Almost 60% of Gram-negative pathogens were ampicillin- and gentamicin-resistant.ResultsA total of 7323 infants with signs or risk factors for sepsis had blood cultures, 2563 had nasopharyngeal swabs, and 23 had lumbar punctures collected. Eleven percent of blood cultures and 8.6% of swabs were positive. Inpatient mortality was 12.1%, with 27.7% case fatality observed among infants with Gram-negative bloodstream infections. Escherichia coli (14.8%), Acinetobacter spp. (10.3%), and Klebsiella spp. (7.6%), were notable contributors to Gram-negative sepsis, whereas Group B Streptococcus was the predominant Gram-positive pathogen identified (13.5%). Almost 60% of Gram-negative pathogens were ampicillin- and gentamicin-resistant.Our study demonstrates high levels of antimicrobial resistance and inpatient mortality from neonatal sepsis in the first months of life in Uganda. This underscores the pressing need for revised, context-specific antimicrobial treatment guidelines that account for the evolving landscape of antimicrobial resistance in neonatal sepsis.ConclusionsOur study demonstrates high levels of antimicrobial resistance and inpatient mortality from neonatal sepsis in the first months of life in Uganda. This underscores the pressing need for revised, context-specific antimicrobial treatment guidelines that account for the evolving landscape of antimicrobial resistance in neonatal sepsis.